Manheimer's cataloging and classification - Saye, Jerry D.; Bohannan, April (New York : Marcel Dekker, 2000)
This work has been revised and updated to include the Anglo-American Cataloguing Rules (2nd ed), the Dewey Decimal System Classification (21st ed) and the Library of Congress Classification Schedules. The text details the essential elements of the International Standard Bibliographic Description; introduces the associated OCLC/MARC specifications; and more.
Includes bibliographical references.
System requirements for accompanying disc: IBM PC and compatible systems.
oif 28/01/15
Ref.
Keywords: Cataloging -- United States -- Problems, exercises, etc; Classification -- Books -- Problems, exercises, etc